Soil moisture and salinity dynamics of drip irrigation in saline-alkali soil of Yellow River basin - Wang, Yaqi; Gao, Ming; Chen, Heting; Fu, Xiaoke; Wang, Lei; Wang, Rui (Frontiers in Environmental Science, 2023)
Soil secondary salinization in the Yellow River Diversion Irrigation Area of Northwest China seriously threatens local agricultural production. Drip irrigation technology is one of the largest contributors to low-yielding saline-alkali land; however, research on the high spatio-temporal scale variability of soil moisture and salinity in drip irrigation is still lacking. Herein, four treatments, CK (flood irrigation, 900 mm), W1 (small volume drip irrigation, 360 mm), W2 (medium volume drip irrigation, 450 mm), and W3 (large volume drip irrigation, 540 mm), were set up to investigate the characteristics and laws of soil moisture and salinity under different irrigation methods. The results showed that the soil moisture of drip irrigation was 5.02%-17.88% (W1), 7.36%-21.06% (W2), and 13.79%-27.88% (W3) higher than that of flood irrigation, resulting in a vertical distribution of soil moisture being low at the top and high at the bottom. Under drip irrigation, the soil salinity formed a desalination zone centered on the drip emitter and this zone gradually expanded to deeper soil with continuous drip irrigation, gradually transforming the soil from surface aggregation type to the bottom accumulation type. The desalination rates of W1, W2, and W3 were 18.46%, 20.84%, and 22.94%, respectively, whereas the salt leaching rate of CK was slower and the salt distribution was not uniform; therefore, the desalination rate was only 5.32%. By precisely controlling the irrigation water volume and flow, drip irrigation significantly reduced surface evaporation and subsurface leakage of water and improved water use efficiency, thus increasing grain yield. Compared with flood irrigation, the yield increase rates of W1, W2, and W3 were 6.6%, 16.18% and 18.32%, respectively. Therefore, drip irrigation with an appropriate irrigation volume in the saline land in northern Ningxia can improve water saving, salt suppression, and maize yield.